The demigod diaries ebook - Riordan, Rick (The Heroes of Olympus, 2012)
What dangers do runaway demigods Luke and Thalia face on their way to Camp Half-Blood? Are Percy and Annabeth up to the task of rescuing stolen goods from a fire-breathing giant who doesn''t take kindly to intruders? How exactly are Leo, Piper, and Jason supposed to find a runaway table, dodge a band of party-loving Maenads (who just might be a little psychotic), and stave off a massive explosion...all in one hour or less? With his trademark wit and creativity, Rick Riordan answers these questions and more in three never-before-seen short stories that provide vital back-story to the Heroes of Olympus and Percy Jackson books. Original art, enlightening character interviews and profiles, puzzles, and a quiz add to the fun in this action-packed collection.